2019
DOI: 10.2147/idr.s184050
|View full text |Cite
|
Sign up to set email alerts
|

<p>Interprofessional Antimicrobial Stewardship Influencing <em>Clostridioides difficile</em> Infection: An 8-Year Study Using Antimicrobial Use Density</p>

Abstract: PurposeTo reduce Clostridioides difficile infection (CDI), we implemented interprofessional antimicrobial, infection control, and diagnostic stewardship (ipAS) conducted by physicians/pharmacists, infection control nurses, and medical technologists, respectively. As a numerical indicator for ipAS, we used antimicrobial use density (AUD) in an 8-year study to validate its efficacy in CDI reduction.Patients and methodsThis was an observational study. CDI was defined as stool samples or C. difficile isolates cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The current study indicated that C. difficile was frequently encountered author keyword in the retrieved literature on AMS [ 50 58 ]. In the 2019 Antibiotic Resistance Threats Report, the U.S. CDC has declared C. difficile infections as an urgent threat [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study indicated that C. difficile was frequently encountered author keyword in the retrieved literature on AMS [ 50 58 ]. In the 2019 Antibiotic Resistance Threats Report, the U.S. CDC has declared C. difficile infections as an urgent threat [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of AMS programs on CDI is controversial. Certain studies indicated that AMS caused a significant reduction in C. difficile infections [ 52 , 53 ] while other studies did not [ 50 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, with the average length of hospital stay as the outcome, the correlation with the average number of beds per pharmacist remained weak ( R = 0.322), even in ARIP 2 hospitals. One reason could be that infection control is often achieved through an integrated approach involving different professionals [ 11 ]. However, various pharmacist-led initiatives have been reported to promote the use of antimicrobial agents, improve achievement rate of effective blood concentration range in vancomycin (VCM) therapy [ 12 ], reducing the rate of MRSA in intensive care units and in antimicrobial allergic reactions [ 13 16 ].…”
Section: Discussionmentioning
confidence: 99%